STRATEGI BERSAING RUMAH MAKAN HENI PUTRI KAILI - Raymondo Wengkau; Chalil Chalil; Maskuri Maskuri (Jurnal Ilmu Manajemen Universitas Tadulako (JIMUT), 2015)
Heni Putri Kaili Restaurant is located at Kaombona Street/ Kampung Nelayan No. 09 Talise, East Palu Sub-district, Palu City. Heni Putri Kaili restaurant has been established since 6 years ago, precisely on February 20th 2010. The owner of the restaurant is Mrs.  Haeni R. Kara , S.Pd. The research intends to find out the competitive level faced by Heni Putri Kaili Restaurant among the restaurant industries in Palu City and to comprehend the alternative strategy that can be used by  Heni  Putri  Kaili  Restaurant.  Data  analysis  methods  used  are  Porter’s  Five  Forces analysis and  the  SWOT  (Strength,  Weakness,  Opportunities,  Threats)  analysis.  Based  on  Porter’s  Five Forces analysis, the study concludes that Heni Putri Kaili restaurant experiences a great rivalry among the restaurant industries in Palu City, which includes the rivalry beetween the competitors from the similiar industry, the suplier’s supplying capacity, and the threat of substitutes products. The  result  of  SWOT  metric  diagram and  IE  table  suggests  that  Heni  Putri  Kaili  Restaurant should  focus on  the  diversifications  strategy  while  improving  the  service  and  the strategy  to increase the promotion of the main product together with other products that are still unfamiliar by the consumers/markets. Heni Putri Kaili Restaurant terletak di Kampung Nelayan No. 09 Talise, Kecamatan Palu Timur,  Kota  Palu.  Restoran  Heni  Putri  Kaili  telah berdiri  sejak  6  tahun  yang  lalu,  tepatnya pada 20 Februari 2010. Pemilik restoran tersebut adalah Nyonya Haeni R. Kara, S.Pd. Tujuan penelitian ini adalah untuk mengetahui kondisi persaingan restoran Heni Putri Kaili di antara industri restoran di Kota Palu dan untuk mengetahui strategi alternatif yang dapat digunakan oleh  restoran  Heni  Putri  Kaili. Metode  analisis  data  yang  digunakan  adalah  analisis Lima Kekuatan  Porter  dan  SWOT  (Strength,  Weakness,  Opportunities,  Threats). Berdasarkan analisis  Lima  Kekuatan  Porter,  dapat  disimpulkan  bahwa persaingan  antara  restoran  Heni Putri  Kaili  di  industri  restoran  di Kota  Palu  mengalami  persaingan  yang  sangat  baik.  Ada banyak faktor; persaingan antara pesaing dari industri serupa, kapasitas penyuplai suplier, dan ancaman  produk  substitusi.  Sebagai  hasil diagram  metrik  SWOT  dan  tabel  IE,  strategi kompetitif  dapat direkomendasikan.  Restoran  Heni  Putri  Kaili  berfokus  pada  Strategi Diversifikasi  dengan  program  strategi  untuk  menegakkan  dan memperbaiki  layanan  dan strategi untuk meningkatkan promosi produk unggulan tanpa meninggalkan produk lain yang masih belum diketahui oleh konsumen / pasar.